Smoking habit of the secondary school age students - Yorulmaz, Hatice; Yeşilyurt, Seçil; Özdilli, Kürşat; Perçin Paça, Ferda (Journal of Dependence, 2009)
Objective: The aim of this study is to determine the smoking frequency of the secondary school age students and to analyze the affecting factors. Methods: This study was performed among 300 students who educated at High School and Primary School in Istanbul. Interview were carried out students concerned with issue. Resuts: In this study, when the smoking status was found, %15 of students were ever smoker; %32.3 of students smoked cigarettes once in a life time. %20.8 of male students and %8.9 of female students were smokers. Friends groups and social environment was determined the most important reason to start smoking %53.3 of students were exposed to smoke where they lived. %55 of student indicated that they didn’t take enough education about the harm of the smoking in their schools, %75 of students took that the all the whole education of the smoking were insufficient. Conclusion: To the result of the analysis we determine that students tried to imitate their friends mostly in smoking behavior, male students more than female students, the most of students didn’t take enough education about the harm of the smoking in their schools and they found out all the whole education of the smoking were insufficient and slight.